Analisa Putaran dan Kemiringan Dinding Saringan untuk Optimalisasi Alat Pemeras Bahan Jamu - Robert Firmandus, I Made Kastiawan (AGROKNOW, 2014)
Abstract. To increase the production of small industry enterprise (home industry) necessary to study and application of appropriate technology (TTG), as an example in household herbal medicine manufacturers. One of the production process is a process that is often a constraint extortion because the process is quite heavy if done manually. In this research, the assessment process is the process of designing a squeeze with centrifugal system. The method used is to do field studies, designing process and analyze theoretically. At the final stage of trials conducted within three (3) conditions that combine the tilt angle of the walls of the filter (extortion) with the amount of rotation. From the tests obtained optimal value tilt angle of the walls of the filter is 680 to 620 rpm rotation, because in this position grater herbal ingredients can be squeezed to the maximum (dryness level) is 96% with the time it takes to lift the dregs fast enough that 21 minutes and the volume filtering is 0.0079 m3 with filtering effectiveness of the prototype is at 72.1%.Keyword: slope of the filter wall, rpm, optimization of extortion, herbal ingredients